ANALISIS RISIKO KELELAHAN KERJA KARYAWAN DI RUANG KLAMBI - Muthohar, Akhmad Muthohar; Tri Purwandari, Aprilia (LPPM Universitas Bina Bangsa, 2024)
Fatigue is a condition of decreased body efficiency that can affect work productivity and cause work accidents. Konveksi Ruang Klambi is considered to not have a good work system because the convection party has problems, especially during working hours. This study conducted a fatigue frequency assessment using the Fatigue Assessment Scale. After identifying the factors and subfactors that cause fatigue, risk control is carried out on each subfactor, an assessment is given based on the severity and possibility of obtaining a risk level that is in accordance with the risk matrix. The results obtained were 9 subfactors that were included in the extreme risk level, with the workload factor whose subfactors overall obtained an extreme risk level. Control efforts based on the control hierarchy were applied to subfactors that obtained an extreme risk level. Overall control efforts were carried out administratively, including the implementation of 8 working hours and 5 working days on subfactors related to time, providing education in the form of posters and stickers to remind of the dangers of fatigue, providing entertainment and sports facilities, designing work scheduling with the application of daily production capacity, 8 working hours a day and 5 working days a week, workers and training for each worker so that they are able to take turns at each work station so that the workload received is evenly distributed.